MALIGNANT BONE TUMORS: A MODERN VIEW OF THE PROBLEM - Arman Khozhayev; Nurkuisa Iles; Yersultan Ordabek; Alissultan Alayev; Nursultan Nurmakhashev; Baglankozha Seitkarim; Olzhas Zhanzakov; Orynbassar Dautakyn; Merey Tassybayev (Research Retrieval and Academic Letters, 2025)
this scientific and analytical work presents modern world and local-regional data on incidence, mortality, lethality rates and five-year survival of such oncological pathology as malignant bone tumors. The issues of etiology and pathogenesis, features of distribution, modern principles of complex diagnostics, as well as prognosis are covered in detail. The epidemiological characteristics of this pathology in our republic are given in the context of regions of the country